Analysis of Composite Skeleton Characteristics of Recycled Asphalt Mixture via Weight Analysis Method - Xiao, Han; Qiu, Yuzhuang; Wu, Kuanghuai; Huang, Wenke; Zhang, Ruida; Chen, Li; Cai, Xu; Luo, Qiang (Frontiers in Materials, 2020)
The aggregate skeleton of hot-mix recycled asphalt mixture comprises reclaimed asphalt pavement (RAP) and new aggregate and is a complex skeleton system containing old and new aggregates. The RAP content in the mixture directly determines the mechanical response characteristics of the composite skeleton, thus affecting the road performance. In order to explore the effect of RAP content on the characteristics of composite skeleton, in this study, the contact points in the composite skeleton were classified into three types: "new-new," "new-old," and "old-old". On the basis of digital image technology and weight analysis methods, the distribution characteristics of the contact type of AC-13 mixture skeletons with different RAP contents were investigated; the correlation between the weight parameters of the contact type and the macroscopic mechanical properties of the mixture was studied. The results indicate that grading is the main factor affecting the total number of contact points; with increasing RAP content, the overall trend of "new-new" contact points is decreasing; the "old-old" contact points increase monotonously and then rapidly after the RAP content reaching 40%; the "new-old" contact points increase first and then decrease with a peak corresponding to 30% RAP. With increasing number of "new-old" contact points, the mechanical indexes of the recycled asphalt mixture enhanced. The weight analysis method can more simply and clearly reflect the correlation between the contact type of coarse aggregate and the mechanical parameters of mixture. In the mixing ratio design of the recycled asphalt mixtures, choosing a mixture with more "new-old" contact points achieved better road performance; therefore, effectively increasing RAP content may be one of the potential ways to enhance road performance.